Insider Trading, Earnings Quality, and Accrual Mispricing - Beneish, Messod D.; Vargus, Mark E. (The Accounting Review, 2002)
This paper investigates whether insider trading is informative about earnings quality and the valuation implications of accruals. We show that (1) the one-year-ahead persistence of income-increasing accruals is significantly lower when accompanied by abnormal insider selling and greater when accompanied by abnormal insider buying; (2) the accrual mispricing phenomenon observed in previous work (e.g., Sloan 1996) is due to the mispricing of income-increasing accruals; (3) one-year-ahead hedge returns to trading strategies based on the direction of accruals and insider trading significantly exceed those based on accruals alone; and (4) the lower persistence of income-increasing accruals accompanied by abnormal insider selling appears to be at least partly attributable to opportunistic earnings management. Our evidence suggests that market participants and researchers can use managers' contemporaneous trading in ex ante assessing the likelihood that the firms' accruals are of high or low quality, and in assessing the likelihood of earnings management. Our evidence suggesting that insiders trade on their knowledge of factors associated with accrual persistence is also relevant to policymakers charged with regulating insider trading.